The effect of network externality on mobile social network site continuance. Issue 3 (6th July 2015) - Zhou, Tao
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the effect of network externality on users' continuance of mobile social network sites (SNS). Design/methodology/approach – Based on the 230 valid responses collected from a survey, structural equation modeling was employed to examine the research model. Findings – The results indicated that network externality, which includes referent network size and perceived complementarity, has a significant effect on perceived usefulness and flow. Privacy concern affects perceived usefulness, flow and privacy risk. These three factors determine continued use. Originality/value – Previous research has focussed on the effects of motivations such as perceived value on user adoption of SNS. The effect of network externality on user continuance has seldom been examined. This research tries to fill the gap.